2002
DOI: 10.1145/513918.513951
|View full text |Cite
|
Sign up to set email alerts
|

RTL c-based methodology for designing and verifying a multi-threaded processor

Abstract: A RTL C-based design and verification methodology is presented which enabled the successful high speed validation of a 7 million gate simultaneous multi-threaded (SMT) network processor. The methodology is centered on statically scheduled C-based coding style, C to HDL translation, and a novel RTL-C to RTL-Verilog equivalence checking flow. It leverages improved simulation performance combined with static techniques to reduce the amount of RTL-Verilog and gate-level verification required during development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…This is in contrast to the work presented in [24], which assumes a one-on-one mapping of registers and variables.…”
Section: Formal Equivalence Criterionmentioning
confidence: 89%
“…This is in contrast to the work presented in [24], which assumes a one-on-one mapping of registers and variables.…”
Section: Formal Equivalence Criterionmentioning
confidence: 89%
“…Model checking of high level programs have existed for some time [15], [16]. There also exist off the shelf and research-level hardware model checkers at the netlist level [17], [18] and at CDFG level [19] with standard logic assertions.…”
Section: Related Workmentioning
confidence: 99%
“…For example, Séméria et al [20] reported verifying C against Verilog as part of a C-based design flow. However, their C model was already in RTL C, so the verification aspect was straightforward.…”
Section: Related Workmentioning
confidence: 99%